Developing a Process for Preference Measures in Pediatric Growth Hormone Deficiency: Challenges and Solutions - Brod M; Pfeiffer KM; Alolga SL; Beck JF; Murphy M; Bruchey AK; Maniatis A; Pitukcheewanont P (Patient Preference and Adherence)
Meryl Brod,1 Kathryn M Pfeiffer,1 Suzanne Lessard Alolga,1 Jane F Beck,1 Morgan Murphy,2 Aleksandra K Bruchey,3 Aristides Maniatis,4 Pisit Pitukcheewanont5 1Health Outcomes Research, The Brod Group, Mill Valley, CA, USA; 2Research & Development, Lumos Pharma, Inc., Austin, TX, USA; 3Clinical Operations, Lumos Pharma, Inc., Austin, TX, USA; 4Pediatric Endocrinology, Rocky Mountain Pediatric Endocrinology, Centennial, CO, USA; 5Chief Medical Officer, Lumos Pharma, Inc., Austin, TX, USACorrespondence: Meryl Brod, The Brod Group, 219 Julia Ave., Mill Valley, CA, 94941, USA, Tel +1 415 381 5532, Fax +1 415 381 0653, Email mbrod@thebrodgroup.netPurpose: Patient experience data capturing the patient voice is gaining increasing recognition across the drug development continuum for use in risk/benefit analysis to evaluate new drugs. The aim of this study was to delineate a prototype process for and then, following this process, develop questionnaires to rigorously assess patient-centric treatment preferences, using pediatric growth hormone deficiency (PGHD) treatment as a model.Patients and Methods: A literature review and concept elicitation interviews with clinical experts (n=5), caregivers of children with PGHD (n=15), and children with PGHD (n=15) were conducted. Most respondents were on injectable treatments with a small subsample on an investigational oral treatment. Data were analyzed based on adapted ground theory, and the GHD-Preference Measure (GHD-PRM), and GHD-Attribute Measure (GHD-ATM) were developed. These questionnaires were cognitively debriefed, refined, and finalized. Best practices for patient-reported outcome measure development and guidelines on assessing patient preferences were followed.Results: Beyond efficacy, some of the most important treatment aspects determining preference for caregivers were the ease of preparation/setup, convenience, and side effects. The most frequently reported reasons for missing, postponing, or changing their child’s medication (eg, dosage) included travel/being away from home and flexibility of dosing. The most frequently reported treatment impacts on children’s daily lives were travel/being away from home, social activities/relationships, and evening routine/schedule. Findings were generally similar between caregivers and children, and those on injectable vs oral treatment. The GHD-PRM is intended for use when treatment comparisons are appropriate; the GHD-ATM is intended for use when treatment comparisons are not available. Each has a caregiver and child version.Conclusion: The GHD-PRM and GHD-ATM can be considered disease-specific prototype preference and attribute questionnaires developed according to a rigorous patient-centric process. Novel, well developed preference measures such as these can provide valuable data to researchers, clinicians, regulators and reimbursement agencies.Keywords: human growth hormone deficiency, quality of life, patient preference, surveys and questionnaires, attribute measure